Nano-particles adapted drilling fluids for the swelling inhibition for the Northern region clay formation of Pakistan - Lalji, S.M. (Springer Science and Business Media Deutschland GmbH, 2021)
Over a past few decades, the major contemplation in the petroleum industry has been to develop a drilling fluid that minimizes the wellbore instability problems and shows high performance in drilling shale formations. This paper focuses on the formulation of a novel water-based drilling fluid using nano-particle graphene oxide (GO) and micron particle Pure-bore in varying concentration ranging from 0.1 to 0.5Â wt. To prove their efficacy, mud containing these particles was used to mitigate the swelling characteristics of the Murree shale formation obtained from the Northern region of Pakistan. Results reveal that the addition of GO and Pure-bore in different concentrations in water-based drilling fluid, significantly improves the rheological properties, filtration characteristics and swelling inhibition of the base mud. Almost 50 swelling of the Murree formation was reduced while using these two particles. Additionally, when the comparison was done between the two particles, it was concluded that GO mud provides a better filtrate control mud and swelling inhibition in the shale formation than Pure-bore. The reason of its better performance is because it develops a better membrane like mud cake having a better surface quality, toughness and stiffness. Moreover, the active functional group especially hydroxyl and carboxyl present in GO interacts actively with Smectite clay mineral with the help of hydrogen and chemical bonds resulting in a better filtration control. These properties of GO ensure that the hydrogen ions do not penetrate into the nano-spacing of the formation thus providing a better wellbore stability in Murree shale formation. Â© 2021, King Abdulaziz City for Science and Technology.